Program Pengabdian Masyarakat Tentang Pentingnya Skrining Vitamin D Dalam Mencegah Sarkopenia Pada Lanjut Usia - Lontoh, Susy Olivia; Alexander Halim Santoso; Valentino Gilbert Lumintang; Fidelia Alvianto; Edwin Destra; Yohanes Firmansyah (Universitas Maritim AMNI Semarang, 2024)
Sarcopenia is a progressive degenerative condition characterized by a decrease in muscle mass, strength, and musculoskeletal function, affecting the quality of life of the elderly. This activity aims to screen for vitamin D and educate the elderly about sarcopenia. Community service activities were carried out in nursing homes, involving education and screening of vitamin D levels. The results showed that the majority of respondents were women (79.6%) with an average age of 74.05 years. Most respondents experienced vitamin D deficiency, with 87.1% deficient, 3.2% adequate, and only 9.7% having good levels, with it being found that more women experienced vitamin D deficiency than men. Education regarding the importance of vitamin D and preventing sarcopenia is provided through outreach sessions and poster media. This activity emphasizes the importance of early detection and comprehensive intervention including physical exercise, proper nutritional intake, and lifestyle modification to prevent sarcopenia and improve the quality of life of the elderly. Community-based interventions are needed to address vitamin D deficiency and promote musculoskeletal health in the aging population.